Influence of pH on the structure and stability of the sweet protein MNEI. Issue 20 (11th October 2016) - Spadaccini, Roberta; Leone, Serena; Rega, Michele Fortunato; Richter, Christian; Picone, Delia
Abstract : MNEI is a single‐chain derivative of the sweet protein monellin that, in recent years, has become an accepted model for studying protein dynamic properties such as folding and aggregation. Although MNEI is very resistant at acidic pH, exposure to neutral or alkaline pH strongly affects its stability. We have performed a thorough NMR study of the dynamic properties of MNEI at different pHs. The results demonstrate that, at physiological temperature, exposure to higher pH increases MNEI flexibility. The changes, originating from a well‐defined region in the protein, are transmitted to the whole structure and are likely to be the key for triggering unfolding processes. Abstract :